Melaleuca armillaris Essential Oil in Combination With Rifaximin Against Staphylococcus aureus Isolated of Dairy Cows - Buldain, Daniel; Gortari Castillo, Lihuel; Buchamer, Andrea Verónica; Aliverti, Florencia; Bandoni, Arnaldo; Marchetti, Laura; Mestorino, Nora (Frontiers in Veterinary Science, 2020)
Staphylococcus aureus is the major subclinical mastitis-causing pathogen in dairy cows. In some European and Latin American countries rifaximin (RIF) is a commonly used therapy at drying off. Phytotherapeutics are alternatives for the treatment of infectious diseases. Melaleuca armillaris essential oil (EO) has been reported as a good antimicrobial against S. aureus. The aim of this work was to investigate, in vitro, the combined effect of EO and RIF to identify a synergic interaction against S. aureus, in order to obtain sufficient information for subsequent pharmacokinetic / pharmacodynamic studies. Minimum Inhibitory Concentration (MIC) for RIF, EO and combinations of this against S. aureus strains were determined at pH 7.4; 6.5 and 5.0, representing intracellular conditions where S. aureus is usually located. Fractional Inhibitory Concentration Index (FIC) and the index of antibacterial activity (E) were evaluated. The MIC of EO at pH 7.4 was 25-12.5 μL/mL and decreased with the acidity of the medium. RIF presented a high antimicrobial activity (0.032 μg/mL) against S. aureus regardless of pH conditions. Combining RIF with EO, we found a synergic effect. A mix of 0.004 μg/mL of RIF and 12.5 μL/mL of EO led to a virtual eradication effect against wild types strains at pH 7.4. Media acidification improves the EO/RIF activity, so EO would be a good adjuvant for RIF to treat staphylococcal infections and decrease antimicrobial resistance.